OPTIMALISASI PEMERIKSAAN KESEHATAN ANAK DI POSYANDU UNTUK MENURUNKAN ANGKA KEMATIAN BAYI - Royani Chairiyah; Mella Yuria RA; Irwanti Gustina (Jurnal Abdi Insani, 2026)
Maternal and child health is one of the key indicators of national health development. Infants and toddlers are vulnerable groups who require optimal health services to support growth and development. However, Indonesia’s infant mortality rate remains relatively high at 23 per 1,000 live births, influenced by low immunization coverage, delayed growth and development screening, and limited utilization of health services. Posyandu plays a strategic role in reducing infant mortality through basic community-level health services. This community service activity aims to increase mothers’ awareness of the importance of routine child health check-ups and to strengthen Posyandu cadres’ skills in monitoring child growth and development. The implementation consisted of preparation, material development and socialization, execution of core activities, and evaluation. Core activities included child health assessment, growth and development monitoring, and health education using audiovisual media and the Maternal and Child Health (MCH) Book. Evaluation was conducted through pre–post tests and observation of cadre involvement. The activity resulted in improved maternal knowledge regarding the importance of child health examinations, with average post-test scores increasing by 40% compared to pre-test. Mothers’ attitudes toward routine check-ups also improved, reflected in increased participation in growth monitoring. Additionally, cadre skills in documenting and using the MCH Book increased by 36%, demonstrated by improved accuracy and completeness of records. Audiovisual education and the MCH Book were effective in enhancing maternal understanding. Overall, the program positively impacted community awareness and strengthened cadre capacity at the Posyandu. The program effectively enhanced maternal knowledge, promoted positive attitudes toward child health examinations, and improved cadre skills, thereby supporting the optimization of MCH services at the Posyandu.